PELATIHAN BACA, TULIS DAN HITUNG UNTUK PENINGKATAN KUALITAS SUMBERDAYA MANUSIA SUKU WANA DI DUSUN KABALO - Quraisyin, Muh. Iqbal; Polonde, Nasry (Jurnal Abdi Insani, 2024)
The Wana tribe is an indigenous community residing in the North Morowali district. Most of their daily activities take place in the forest of Kabalo. However, social inequality, especially in terms of access to education, is a significant concern for PKBM Kasintuwu Anta in eradicating illiteracy. Therefore, they have started conducting reading, writing, and counting training activities to address the issues that exist in the Wana tribe. The primary objective of these activities is to manage educational potential, particularly educational corridors that meet the community's requirements and prioritize the participation of the village community. By providing a positive impact on the education of the Wana tribe, it will enable them to read, write, and count, which is the primary step in eradicating illiteracy, the foundation of knowledge to advocate against social problems in indigenous communities. These activities were implemented between January and December 2018, with methods that include socialization, provision of learning equipment, and training in reading, writing, and counting. The results of this activity have helped the Wana tribe in writing, reading, and counting, motivating them to realize the importance of basic education, particularly among children learners.